Pendidikan keagamaan di masyarakat multikultural: Peran sosial dan keagamaan Kyai Muhammad Sukemi di Yosodadi Metro - Malindra, Malindra; Muslimin, Ahmad; Syaifullah, Muhammad (Kuras Institute, 2025)
Purpose − Religious figures have an important and noble role in social life. The purpose of this study is to determine the role of Kyai Muhammad Sukemi as a religious figure in religious education in Yosodadi and the obstacles he faces. Method − This research is a qualitative study with data collection in the form of observation, interviews, and documentation. The data obtained in the field is explained descriptively, in depth and thoroughly with Structural Functionalism Theory-Talcott Parsons as the analysis knife. Findings − The results showed that there was a big role of Kyai Muhammad Sukemi in religious education in the community in Yosodadi, Metro city. Kyai Muhammad Sukemi is a charismatic figure, highly trusted and a role model by the community. In addition, it was found that the social role of Kyai Muhammad Sukemi was carried out by mingling with the community, establishing a relationship between the kyai and the community well, the role of Kyai Muhammad Sukemi in religious education was not only in NU activities, he also held regular studies attended by congregants both weekly and monthly, sholawatan, children's recitation and other social services. Therefore, his involvement has a positive impact on the community.